The effect of Mahāyāna Puja Bakti and emotional intelligence on the spiritual intelligence of Buddhists at the Padmasari Temple in Lahat, South Sumatra - Widhi Nyanna Pujita; Supartono; Tjhia Khie Khiong (SMARATUNGGA: JURNAL OF EDUCATION AND BUDDHIST STUDIES, 2021)
Buddhists perform Mahāyāna puja bakti as a form of respect (pūjā) and devotion to the Buddha, Bodhisattva, and Mahāsattva. This study aims to analyze the effect of Mahāyāna puja bakti service and emotional intelligence on spiritual intelligence. This research method uses a quantitative approach. The research design used is explanatory. The sample in this study were 60 Buddhists and youth at Padmasari Temple in Lahat. The results of the research data analysis show that Mahāyāna puja bakti and emotional intelligence have a significant effect on spiritual intelligence. Based on the results of this study, the fact that Mahāyāna puja bakti was carried out regularly and high emotional intelligence can increase the spiritual value of Buddhists.